Pengaruh Lingkungan Sosial terhadap Integritas Pegawai pada Organisasi Perangkat Daerah (OPD) Kabupaten Tanah Datar - Muthmainnah Muthmainnah; Syamsir Syamsir (Faculty of Social Science, Universitas Negeri Padang, 2022)
This study’s purpose was to identify : (1) the effect of family environment on employee integrity in OPD Tanah Datar Regency; (2) the effect of school environment on employee integrity in OPD Tanah Datar Regency; (3) the effect of community environment on employee integrity in OPD Tanah Datar Regency; (4) the effect of an environment of family, environment of the school, and environment of the community simultaneously on employee integrity in OPD Tanah Datar Regency. The background of this research was because there were still many employee integrity problems found in the OPD of Tanah Datar Regency. This research type was quantitative research using statistical analysis. The research variable used the independent variable, namely the social environment, while the dependent variable was integrity. This research population was employees at the OPD Tanah Datar Regency. The total sample in the study amounted to 97 employees. The technique for data collection in this research was a questionnaire distributed to respondents through the measurement of the Likert scale. The research analysis uses a multiple linear regression test using SPSS software version 26.0. The research results indicated that: (1) There was a significant influence of the family environment on the integrity of employees in the OPD of Tanah Datar Regency. (2) There was a significant influence of the school environment on the integrity of employees in the OPD of Tanah Datar Regency. (3) There was a significant influence of the environment of the community on the integrity of employees in the OPD of Tanah Datar Regency and (4) There were significant influences of the environments of family, school, and community simultaneously on the integrity of employees in the OPD of Tanah Datar Regency.